Statistical study of the alteration of the magnetic structure of magnetic clouds in the Earth's magnetosheath. Issue 3 (7th March 2017) - Turc, L.; Fontaine, D.; Escoubet, C. P.; Kilpua, E. K. J.; Dimmock, A. P.
Abstract: The magnetosheath plays a central role in the solar wind‐magnetospheric coupling. Yet the effects of its crossing on solar wind structures such as magnetic clouds (MCs) are generally overlooked when assessing their geoeffectivity. Using 82 MCs observed simultaneously in the solar wind and the magnetosheath, we carry out the first statistical study of the alteration of their magnetic structure in the magnetosheath. For each event, the bow shock properties are obtained from a magnetosheath model. The comparison between the model results and observations shows that in 80% of cases, the MHD‐based model captures well the magnetosheath transition; the other events are discussed separately. We find that just downstream of the bow shock the variation of the magnetic field direction shows a very good anticorrelation ( r =− 0.91) with the angle between the upstream magnetic field and the shock normal. We then focus on the magnetic field north‐south component B z because of its importance for geoeffectivity. Although the sign of B z is generally preserved in the magnetosheath, we also find evidence of long‐lasting intervals of opposite B z signs in the solar wind and the magnetosheath during some events, with a | B z | reversal >10 nT at the magnetopause. We find that these reversals are due to the draping of the field lines and are associated with predominant upstream B y . In those cases, the estimated position of the regions of antiparallel fields along the magnetopause is independent of the sign of the upstream B z . This may have strong implications in terms of reconnection. Key Points: We study the modification of the magnetic field direction of 82 magnetic clouds (MCs) across the bow shock and in the magnetosheath Their magnetic field direction varies significantly across the quasi‐parallel shock, and the sign of B z can change in the magnetosheath Changes in the sign of B z are associated with a large B y, suggesting that this component may also affect the geoeffectivity of a MC